2014
DOI: 10.1111/add.12690
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in personality traits explains genetic overlap between borderline personality features and substance use disorders

Abstract: Aims To examine the genetic overlap between borderline personality features (BPF) and substance use disorders (SUDs) and the extent to which variation in personality traits contributes to this covariance. Design Genetic structural equation modelling was used to partition the variance in and covariance between personality traits, BPF, and SUDs into additive genetic, shared, and individual-specific environmental factors. Setting All participants were registered with the Australian Twin Registry. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…However, our confidence intervals span their estimated 50% of total genetic variance explained by antisocial PD in Wave 2 AUD. The moderate genetic correlation we found between borderline PD and Wave 1 AU is commensurate with a recent report finding the genetic correlation with alcohol abuse-dependence to be .33 (Few et al, 2014). This correlation was slightly higher for Wave 1 AUD and Wave 2 AU (.41-.44), and highest for Wave 2 AUD (0.75).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our confidence intervals span their estimated 50% of total genetic variance explained by antisocial PD in Wave 2 AUD. The moderate genetic correlation we found between borderline PD and Wave 1 AU is commensurate with a recent report finding the genetic correlation with alcohol abuse-dependence to be .33 (Few et al, 2014). This correlation was slightly higher for Wave 1 AUD and Wave 2 AU (.41-.44), and highest for Wave 2 AUD (0.75).…”
Section: Discussionsupporting
confidence: 91%
“…This correlation was slightly higher for Wave 1 AUD and Wave 2 AU (.41-.44), and highest for Wave 2 AUD (0.75). In terms of sources of covariation, Few et al (2014) found that the association between borderline and alcohol abuse-dependence was attributable to genetic risk factors only in the absence of neuroticism. Likewise, Distel et al (2012) found the association between heavy AU and borderline PD to be attributable largely to unique environmental risks.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and Sher (1994) found that familial risk for alcoholism was associated with high negative emotionality. Furthermore, negative emotionality is moderately heritable (Scott et al, 2016), and there is evidence of genetic overlap between negative emotionality and AUP (Few et al, 2014). One study of young adults found that associations between single nucleotide polymorphism(s) (SNP) in nicotinic acetylcholine receptor genes and alcohol and nicotine dependence-as defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV; American Psychiatric Association, 1994)-were partially mediated by high negative emotionality (Criado et al, 2014).…”
mentioning
confidence: 99%
“…[5][6][7] Patients experiencing a positive effect after a drug administration who simultaneously exhibit higher levels of specific personality traits, such as neuroticism or impulsivity, are thought to be at a higher risk of developing drug addiction. 32,33 However, we could not prove any risk factor for a euphoric propofol reaction. On the other hand, we identified slight differences regarding personality: None of the CURP patients showed above average conscientiousness, while 15% of the CERP patients did so.…”
Section: Discussionmentioning
confidence: 60%